Milk and dairy products – a scoping review for Nordic Nutrition Recommendations 2023 - Kirsten Bjørklund Holven; Emily Sonestedt (Food & Nutrition Research)
Milk and dairy products are major sources of protein, calcium, and other micronutrients. Milk and dairy products contribute with approximately half of the total intake of saturated fat in the Nordic and Baltic diets. Saturated fat is an important determinant of plasma total and low density lipoprotein (LDL)-cholesterol concentrations, and a causal relationship between high LDL-cholesterol and atherosclerotic cardiovascular disease has consistently been documented. The aim of this scoping review is to describe the evidence for the role of milk and dairy products for health-related outcomes as a basis for setting and updating food-based dietary guidelines. Two qualified systematic reviews were included (World Cancer Research Fund and a systematic review for the US Dietary Guidelines Advisory Committee 2020). In addition, systematic reviews published between January 2011 and January 2022 were considered, screened (555 records) and evaluated (159 records) for this review. The systematic reviews suggest that milk or dairy consumption is not associated with increased risk of cardiovascular disease and dyslipidaemia. Current evidence suggests an inverse association with some cardiometabolic risk factors, such as total and LDL-cholesterol, especially regarding fermented dairy products (i.e. yogurt and cheese). There was evidence of an association between intake of dairy products and reduced risk of colorectal cancer. Some studies reported an inverse association between intake of dairy and type 2 diabetes or markers of impaired glucose homeostasis, especially for low-fat dairy, yoghurt, and cheese. Most studies suggest that intake of milk or dairy is not associated with increased risk of cardiovascular risk and some suggestions of inverse association, especially with low-fat products and fermented dairy products, were found with respect to cardiovascular disease, type 2 diabetes, and colorectal cancer. Milk or dairy products are important dietary sources of calcium and iodine, and are fully compatible with a healthy dietary pattern.